DETERMINACIÓN DEL DOSAJE DE TROMBOSPONDINA (TSP) EN PLASMA Y SALIVA EN PACIENTES CON HIV/SIDA CON ALTERACIONES ENDOBUCAL - Taboada Vega, Manuel (2004)
This investigation included 65 samples unfolded into 15 students of 20 to 26 years old, selected from Faculty Of Odontology, appcv-ently healthy; 50 patiens infected whith VIH/AIDS; 10 ofthemfrom Al to A3, 17 from Bl to B3, and 23 from el toC3 (CDC clasisification systen 1993). Thrombospondine dosage (TSP1) in plasm 0.25 to 4ug/ml. And in saliva, 4to 5 ug/ml from the control group. Thrombospondine (TSP1) in saliva ofVIH/AIDS patiens, 10 to 35 ug/ml; spit PH 6,50 to 6,70 in the control grou; in the smple ofVIH/AIDS patint ph 6.8to 7.0. The candidiasis evolves progressively prevailing the pseudo membranous type. The saliva flow and the periodontal process (gingivitis). As a constant, the caries process emigration deteriorate$ progressively, as a consequence fa the immune response deerease, aggravating the clinic bolser (buccal pathology). Evultion period of opportunistic infections, is directly proportional with the bucal pathology. (TSP1)in saliva and plasm- VHI/AIDS-SALIVA pH.